Asertividad en Estudiantes de la Institución Educativa Teófilo Roberto Potes de Buenaventura, Valle del Cauca, 2021 (2021)
The objective of this research work was to evaluate the assertiveness style presented by the students of the Teófilo Roberto Potes Educational Institution of Buenaventura, Valle del Cauca, with a non-probabilistic convenience sampling, composed of 33 students between 15 and 17 years of age, by means of a non-experimental descriptive quantitative method and an analytical empirical epistemological criterion. In order to answer the objectives, a sociodemographic characterization survey was used and the Multidimensional Assertiveness scale by Mirta Margarita Flores Galaz and Rolando Díaz Loving -2004 composed of 45 statements and 5 likert-type response options that allow knowing the assertiveness style: indirect assertiveness, non-assertiveness and assertiveness, the result was that most of the students are located with the style of non-assertiveness and assertiveness.